ORGANIZATIONAL AND LEGAL BASIS OF THE PROCESSES OF ORGANIZING AND CONDUCTING CONTINUOUS PROFESSIONAL PRACTICE OF STUDENTS (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
Continuing professional practice is an important component of students' education, providing them with real-world experience and practical skills necessary for their future careers. The organization and conduct of continuous professional practice requires a solid organizational framework and compliance with legal regulations to ensure the quality and effectiveness of the educational experience. Institutions need specific placement offices or departments responsible for coordinating student placement.[1]